Optimization of media components for tetrathionate hydrolase production from thiobacillus ferrooxidans - Yusof, Faridah; Mohd Dom, Azratul Ashimah Nur (Journal of Pure and Applied Microbiology, 2014)
Tetrathionate hydrolase produced by Thiobacillus ferrooxidans has been known to be the enzyme responsible in the devulcanization of used rubber prior to recycling. The aim of this study was to statistically obtain a model that would yield an optimized media concentrations for the best production of this bacterial enzyme. One-factor-at-a-time (OFAT) experimental design was applied to find the possible optimum range of five media components. Based on the OFAT results, a face centered central composite design (FCCCD) by Design Expert? 6.0.8 was applied using a 4-factors, 3-center points to find the optimum media concentrations to yield the highest tetrathionate hydrolase. Response Surface Methodology (RSM) predicted the level of factors for maximized response. In this study, it is concluded that the medium containing 0.4g/L MgSO4.7H2O, 4.0g/L (NH4)2SO4, 2.0g/L Na2S2O3.5H2O and 3.0 g/L KH2PO4 results in the production of the highest specific activity of tetrathionate hydrolase (295.7 U/mg Protein). Other parametric conditions used were 0.25g/L for CaCl2.2H2O with an initial pH buffer of 4, incubated at 25oC while agitating at a speed of 125 rpm. Keywords : Thiobacillusferrooxidans, tetrathionate hydrolase, OFAT, FCCCD, devulcanization of rubber.